The Weather of the Agulhas bank and the Cape South Coast - Hunter, I T (Department of Oceanography, 2016)
Until 1982, when the National Research Institute for Oceanology (NRIO) erected self-contained, automatic weather stations (AWS) on the Cape South Coast, no continuous coastal measurements were available. This Institute had erected an AWS on the drilling rig Sedco K in 1978, so that over 3 years of very valuable off- shore data was already available on the adjacent Agulhas Bank. Al though the weather offices at George and Port Elizabeth have made accurate meteorological observations for over 30 years, this data is shown here to differ significantly from actual coastal measurements. Thus the NRIO AWS network, which operated for just over a year, provided a detailed, short-term data set for the study of coastal weather processes. In order to acquire longer term data from coastal observations, five years of hourly wind observations from lighthouse keepers along the Cape South Coast were also utilised. Although these are estimates, it is shown that a coastal estimate may be more representative of marine conditions than an anemometer reading some distance inland. Voluntary Observing Ship's data (VOS) extracted from SADCO's Marine Climatology database, provided the long-term offshore information, whilst also supplying very useful 'present weather' (synoptic code ww) observations for case studies. Observations from synoptic stations for the period that the coastal AWS were deployed (February 1982 - March 1983), were provided by the South African Weather Bureau. With this unique and comprehensive data set, the various weather systems affecting the region are discussed. Twelve case studies form the main reference for this discussion, which includes relevant oceanographic parameters. The weather systems are considered firstly as individually propagating circulations with the AWS network providing details of propagation speeds and coastwise development. Secondly the combined 'weather producing' effects of these systems are discussed, with a strong emphasis being placed on man/weather interactions. It is shown that certain operations along the Cape South Coast and over the Agulhas Bank, are extremely weather sensitive, and would benefit considerably from an increased knowledge of weather processes. Recommendations aimed not only at those managing weather sensitive operations, but also at those involved in coastal meteorological measurement and research, complete the thesis.